Trade Openness-Economic Growth Nexus: Empirical Evidence from Nigeria - Nurudeen, Abu; Obi, Ben; Wafure, Gobna Obida; Jimaza, Michael; Abdullahi, Usman; Gana, Usman (Economic Journal of Nepal, 2015)
The paper empirically investigates the relationship between trade openness and economic growth in Nigeria from 1970 to 2008 using the error correction method. The paper also considers other potential determinants of growth such as human capital development, infrastructural development, international capital inflows, and debt service. The regression results show that trade openness has a significant negative effect on economic growth. Other important variables that have a significant influence on growth include debt service and human capital development. The recommendations therein include among others the following: employment of appropriate trade policies (with certain restrictions) that promote exports relative to imports and expansion of the manufacturing and services sectors so that Nigeria can benefit more from trade; increasing government expenditure on human capital development in the form of investment in education, health and other community services as well as other infrastructural services like roads, power telecommunications etc; and adoption of strategies that would lead to the attraction of more international capital. The Economic Journal of Nepal, Vol. 35, No. 3, July-September 2012 (Issue N0. 139)